Theology and creed in Sunni Islam: the Muslim Brotherhood, Ash'arism, and political Sunnism - Halverson, Jeffry R. (Palgrave Macmillan, 2010)
This book explores the correlation between anti-theological thought and the rise of Islamism in the twentieth century by examining Egypt's Muslim Brotherhood and the leadership of Umar al-Tilmisani (d. 1986)